Percepción y expectativa de los ciudadanos peruanos frente al gobierno electrónico - Cardona, Diego (2004)
This work presents how Peruvian citizens evaluate government efforts to implement e-government initiatives. First, the basic concepts used in the article are described, then the Peruvian e-government policy is briefly exposed, and it ends up by measuring how citizens perceive e-government and what they expect from it, through a model developed by the author during his doctoral research (Cardona, 2004). The model includes five latent and independent constructs: attitude, aptitude, confidence, relevance, and satisfaction, which affect two latent and dependent constructs: the citizen's perception and expectation regarding their interaction with public administration using information technologies and communication, under the effect of illustrative variables related to citizens, institutions and the environment.